Digital marketing strategies for tourism, hospitality, and airline industries - Santos, Jose Duarte, 1966-; Silva, Oscar Lima, 1970- (Advances in marketing, customer relationship management, and e-services (AMCRMES) book series., 2020)
""This book examines the influence digital marketing on the consumer relationship in the fields of tourism, hospitality. and airline industries"--Provided by publisher"--